Classroom Activities and Student Motivation in Learning an English Subject: A Case Study at a Public Secondary School in Cambodia - Saban Bon; Tive Sorn; Mab Mon; Mon Muon; Malis Mon (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
This study sought to investigate students’ perceptions of classroom activities and their motivation levels in learning an English subject. The study also examined the affiliation between classroom activities and student motivation. The survey questionnaires were employed to collect the data from 120 upper secondary graders studying at a public secondary school in Cambodia. Social Science Version 16.0 (SPSS 16.0) was utilized to analyze. Descriptive statistics and Pear Product Moment Correlation were performed. The results revealed that EFL teachers frequently employed ‘Mechanics’ and ‘Exclusive Use of Language’ in their teaching. The results apropos of student motivation indicated that students had a higher level of motivation in ‘Confidence’, and ‘Motivation about Language’ and the lowest level in ‘Motivation about Class’. The result also revealed that ‘Fun’ positively correlates with ‘Confidence’ and ‘Motivation about Class’. Conversely, ‘Mechanics’ is negatively correlated with ‘Motivation about Class’. Therefore, the study argued that the teachers less frequently employed ‘Fun’ activities that could boost student motivation. In contrast, ‘The teachers commonly practiced mechanics’ activities that could decrease student motivation. In this sense, the study suggested that teachers maximize ‘Fun’ activities and minimize ‘Mechanics’ activities. However, because of the weak and moderate correlation between classroom activities and students’ motivation, the level of student motivation was not mostly determined by classroom activities. Thus, scrutiny of other factors enhancing the level of student motivation could be a topic for future study.